Analysis of risk factors related to extremely and very preterm birth: a retrospective study - Xiaohong Ji; Chengqian Wu; Min Chen; Lili Wu; Ting Li; Zhijing Miao; Yan Lv; Hongjuan Ding (BMC, 2022)
Abstract Background: Preterm birth is one of the main causes of perinatal morbidity and mortality and imposes a heavy burden on families and society. The aim of this study was to identify risk factors and analyze birth conditions and complications of newborns born at < 32 gestational weeks for extremely preterm (EP) and very preterm (VP) birth in the clinic to further extend the gestational period. Methods: We performed a retrospective cohort study and collected data from 1598 pregnant women and 1660 premature newborns (excluding 229 premature babies who died due to severe illness and abandonment) admitted to the Obstetrics and Gynecology Hospital Affiliated with Nanjing Medical University in China from 2016 to 2020. We compared women's and newborns' characteristics by t-tests and Chi-square tests for continuous and categorical variables, respectively. Multivariable logistic regression was performed to estimate the effects of risk factors on EP and VP birth. Results: We identified 3 independent risk factors for EP birth: cervical incompetency (P < 0.001); multiple pregnancy (P < 0.01), primipara (P < 0.001). Additionally, we identified 4 independent risk factors for VP birth: gestational diabetes mellitus (GDM) (P < 0.05), preterm premature rupture of membrane (PPROM) (P < 0.01), fetal intrauterine distress (P < 0.001), and hypertensive disorder complicating pregnancy (HDCP) (P < 0.001). In addition, pairwise comparisons revealed statistically significant differences in the incidence rates of neonatal pneumonia, bronchopulmonary dysplasia (BPD) and sepsis between the 28-28 + 6 and 29-29 + 6 weeks of gestation groups (P < 0.05). Compared with 28-28 + 6 weeks of gestation, neonatal complications were significantly more common at < 26 weeks of gestation (P < 0.05). The incidence rates of neonatal intracranial hemorrhage(NICH), patent ductus arteriosus(PDA), patent foramen ovale(PFO), pneumonia, BPD and sepsis were significantly higher in the 26-26 + 6 and 27-27 + 6 gestational weeks than in the 28-28 + 6 gestational weeks (P < 0.05). Conclusion: PPROM, is the most common risk factor for EP and VP birth, and cervical insufficiency, multiple pregnancy, and primipara are independent risk factors for EP birth. Therefore, during pregnancy, attention should be devoted to the risk factors for PPROM, and reproductive tract infection should be actively prevented to reduce the occurrence of PPROM. Identifying the risk factors for cervical insufficiency, actively intervening before pregnancy, and cervical cervix ligation may be considered to reduce the occurrence of EP labor. For iatrogenic preterm birth, the advantages and disadvantages should be carefully weighed, and the gestational period should be extended beyond 28 weeks to enhance the safety of the mother and child and to improve the outcomes of preterm birth.